2019
DOI: 10.1021/acsnano.9b03444
|View full text |Cite
|
Sign up to set email alerts
|

Metal-Ion Modulated Structural Transformation of Amyloid-Like Dipeptide Supramolecular Self-Assembly

Abstract: The misfolding of proteins and peptides potentially leads to a conformation transition from an αhelix or random coil to β-sheet-rich fibril structures, which are associated with various amyloid degenerative disorders. Inhibition of the β-sheet aggregate formation and control of the structural transition could therefore attenuate the development of amyloid-associated diseases. However, the structural transitions of proteins and peptides are extraordinarily complex processes that are still not fully understood a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
141
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(146 citation statements)
references
References 66 publications
5
141
0
Order By: Relevance
“…Recently, Ji et al [38] [40]. Stupp et al [41] showed that hydrogen bonding, π-π, and hydrophobic interactions all tend to promote the aggregation of amphiphilic peptide molecules, whereas electrostatic repulsion causes their disassociation.…”
Section: Electrostatic Interaction Screened Coulombic Interactions Bmentioning
confidence: 99%
“…Recently, Ji et al [38] [40]. Stupp et al [41] showed that hydrogen bonding, π-π, and hydrophobic interactions all tend to promote the aggregation of amphiphilic peptide molecules, whereas electrostatic repulsion causes their disassociation.…”
Section: Electrostatic Interaction Screened Coulombic Interactions Bmentioning
confidence: 99%
“…Different chemical reactions are employed to construct selfassembled nanostructures . A general approach followed by peptide chemists is to incorporate modifications in the form of easy and reversible cleavable appropriate moieties/groups at the carbonyl-nitrogen bond (readily cleavable urethanes containing appropriate alkyl groups such as benzyl and tert-butyl liberating the amino groups), incorporating alkyl spacers of various lengths to modulate the chirality (Panda et al, 2019), π-clamping to tune the reactivity , backbone amide modifications for peptidomimetic hydrogelators with enhanced stability and mechanical properties compared to peptide hydrogelators (Basavalingappa et al, 2019), enforcing a conformational constraint to prevent β-sheet structure (Bowerman and Nilsson, 2010), formulated sequence patterns to optimize charge distribution for conjugating bioactive cargo , alternating d/l-chirality for 1D-to 2D-selfassembly (Insua and Montenegro, 2019), a racemic mixture of the mirror-image peptides to provide more rigidity to the gel (Nagy-Smith et al, 2017), alternative hydrophobic and hydrophilic residues for catalytic activity (Song et al, 2018), coordination with metal ions to inhibit amyloid-like structure (Ji et al, 2019), fine-tune assembly for hydrogel (Loic, 2017) and so on. N-Acetylation (compound attached to the amino; N-terminus) and C-amidation (compound attached to the carboxyl; C-terminus) is the most usual policy to stabilize nearly all categories of peptides.…”
Section: Impact Of Chemical Modificationsmentioning
confidence: 99%
“…The molecular mechanism build on density functional theory, advised by González-Díaz et al recommends the position of the side chain, where it branches, during crystallization, to be the determining factor to drive the dipeptides into either hydrophobic or hydrophilic channels (González-Díaz et al, 2019). The structural transformation of a dipeptide self-assembly just by changing the types/ratios of the metal ion or the dipeptide to inhibit amyloid-like structure has been presented by Ji et al (2019).…”
Section: Dipeptides For Biologics Deliverymentioning
confidence: 99%
“…As a result, metal ions have been widely exploited to promote peptide self-assembly in vitro and for the de novo design of functional proteins. [26,[49][50][51][52][53][54][55][56][57][58] In these cases, metal ion complexation serves as a force distinct from the non-covalent interactions already discussed in specific binding ligands and preferred coordination geometry. By substituting two His residues for the two Asn residues of NN, we expect the self-assembly of HH to be controlled by metal-ion coordination in the hydrophobic interface instead of specific Asn-Asn interactions.…”
Section: Self-assembly Of Hh and Responsiveness To Metal Ionsmentioning
confidence: 99%